Bacterial nucleoid-associated protein HU as an extracellular player in host-pathogen interaction - Stojkova, Pavla; Spidlova, Petra (Frontiers in Cellular and Infection Microbiology, 2022)
HU protein is an important regulator of bacterial virulence, pathogenesis and survival. Its indispensable role in DNA-related processes in bacteria was described. HU protein is a necessary bacterial transcription factor and is considered to be a virulence determinant as well. Less is known about its direct role in host-pathogen interactions. The latest studies suggest that HU protein may be secreted outside bacteria and be a part of the extracellular matrix. Moreover, HU protein can be internalized in a host cell after bacterial infection. Its role in the host cell is not well described and further studies are extremely needed. Existing results suggest the involvement of HU protein in host cell immune response modulation in bacterial favor, which can help pathogens resist host defense mechanisms. A better understanding of the HU protein's role in the host cell will help to effective treatment development.